Method for detecting mixing content of solid electrolyte in battery pole piece

Through various characterization methods, the distribution and content of solid electrolytes in the battery electrode sheet is detected, and the problem of insufficient detection accuracy in the prior art is solved, and high-precision blending content detection is achieved, supporting battery performance and safety optimization.

CN119438185AActive Publication Date: 2025-02-14INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411625476.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect the blending content of solid electrolytes in battery poles, affecting battery performance and safety.

Method used

By combining morphology, structure and component characterization methods, including scanning electron microscope, energy dispersion X-ray spectrometer and X-ray diffractometer, the electrode cross-section and powder sample are detected to determine the distribution and content of solid electrolytes.

Benefits of technology

It realizes high-precision detection of the solid electrolyte blending content in the battery electrode sheet, with an error of less than 10%. It is suitable for various battery cell types, providing a basis for optimizing the performance of the electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438185A_ABST
    Figure CN119438185A_ABST
Patent Text Reader

Abstract

The invention relates to a method for detecting the mixing content of a solid electrolyte in a battery pole piece. The method comprises the following steps: preparing at least one pole piece section test sample in each sampling area of the battery pole piece to be detected; acquiring image data of each pole piece section test sample, determining whether characteristic solid particles exist in each pole piece section test sample or not based on contrast parameters of the image data, and determining whether the battery pole piece is mixed with the solid electrolyte or not according to the proportion of the pole piece section test sample with the characteristic solid particles; performing element type characterization test on each pole piece section test sample to obtain characteristic elements of characteristic solid particles; performing separation treatment on the surface coating layer of the sampling area to obtain a powder sample, performing characterization, determining the type of the mixed solid electrolyte, and obtaining a molecular formula of the solid electrolyte; and determining the content of characteristic elements of the solid electrolyte mixed in the powder sample, and determining the mixing content of the solid electrolyte in the battery pole piece by combining the molecular formula of the solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery material analysis, and in particular to a method for detecting the content of solid electrolyte blending in a battery pole piece. Background Art

[0002] In recent years, solid-state battery technology has attracted widespread attention in the industry as an electrochemical energy storage technology that can achieve both high specific energy and high safety, but its development still faces many challenges. On the positive electrode side, high-voltage positive electrode materials have the problem of positive electrode interface instability under high voltage. For example, LiNi 1-x Co x / 2 Mn x / 2 O2 high nickel layered materials are widely used due to their high mass energy density and volume energy density. 3+ / Ni 4+ The instability of the + / Li), can only achieve 60%-70% of the theoretical capacity. On the negative electrode side, lithium metal negative electrodes have problems such as dendrite growth and interface reaction, which poses great challenges. Taking sulfide solid electrolytes as an example, most sulfide solid electrolytes are unstable to lithium metal. During the battery charge and discharge cycle, there are problems such as dendrite growth and electrode / electrolyte interface instability, which in turn lead to increased internal resistance, reduced Coulomb efficiency, internal short circuit and eventual battery failure. The above interface problems between the positive and negative electrodes seriously hinder the practical application of solid-state batteries.

[0003] Existing research results show that solid electrolyte blending is an effective means to solve the electrode / interface problem in solid-state batteries. 6.7 LqCy 1.7 Ta 0.3 O 12 Mixed Li Ni 0.6 Mn 0.2 Co 0.2 The composite cathode of O2 can work stably under high voltage, and Li 6.7 LqCy 1.7 Ta 0.3 O 12 It can not only passivate the interface layer, but also remove protons and water in the electrolyte. 5wt% Li 6.7 LqCy 1.7 Ta 0.3 O 12 Mixed Li Ni 0.6 Mn 0.2 Co 0.2The O2 composite positive electrode effectively improves the electrochemical performance of the whole battery. In addition, the lower the lithium content in the positive electrode (i.e., the higher the state of charge), the worse the structural stability and the greater the amount of oxygen released at high temperature. 6.5 LqCy 1.5 Ta 0.5 O 12 , which can provide lithium ions for the layered oxide cathode in the charged state at high temperature. This relithiation process increases the content of Li in the delithiated LiCoO2, thereby significantly delaying the structural decomposition and oxygen release, and improving the thermal stability of Li CoO2. A small amount (1wt.%) of Li 6.5 LqCy 1.5 Ta 0.5 O 12 The safety performance of LiCoO2 / graphite full battery can be significantly improved. On the negative electrode side, by introducing soft carbon-cubic phase nano-Li 6.4 LqCy 1.4 Ta 0.6 O 12 The interfacial layer combines the advantages of soft carbon as a three-dimensional host material and the cubic phase Li 6.4 LqCy 1.4 Ta 0.6 O 12 The high ionic conductivity / diffusion coefficient and stability to metallic lithium provide sufficient space for lithium deposition, effectively solving the interface incompatibility problem of ion-conductive solid electrolyte / lithium metal and avoiding the occurrence of side reactions, which provides a feasible and scalable method for optimizing the interface between sulfide solid electrolyte and lithium metal anode.

[0004] Unlike other complex coating processes, the solid electrolyte blending method is easy to implement in commercial lithium-ion batteries due to its manufacturing friendliness, energy saving and cost-effectiveness. The blending of solid electrolyte powder as a modified material with the positive electrode material is one of the applications with the highest market recognition and the fastest industrialization process. When preparing blended pole pieces, the amount of solid electrolyte blending will affect the charge transport channel, that is, it will affect the ability to provide electrons / ions to the positive / negative electrode area. The preparation of high-performance solid-state battery blended pole pieces requires consideration of the optimal composition of relevant parameters, such as the distribution of active materials and solid electrolytes, and the mass proportion of each component, in order to achieve high energy and power density, while minimizing residual pores and ensuring good electron / ion transmission capabilities.

[0005] At present, the content of solid electrolyte blending in the pole piece is generally controlled within 5wt% or less. Accurately characterizing the uniformity of the distribution of trace solid electrolytes in the blended pole piece, the blending content, and the change of the content during the electrochemical cycle is an effective supporting technology for improving the blending effect of the pole piece and optimizing the performance of the blended pole piece. At present, no reports have been found on the detection method of the blending content of solid electrolytes in the pole piece. Summary of the invention

[0006] The purpose of the present invention is to provide a method for detecting the content of solid electrolyte blending in battery pole pieces in view of the defects existing in the prior art. The method can effectively detect the distribution and content of solid electrolyte in blended pole pieces by utilizing a variety of characterization methods such as morphology, structure and composition. The detection method of the present invention is versatile and has high detection accuracy, with a detection error of less than 10%. It can be applied to pole piece samples, as well as original pole pieces in various battery cells such as soft-pack battery cells, hard-shell battery cells, cylindrical battery cells, and pole piece detection after electrochemical cycling. It can be used to optimize the analysis of pole piece blending with solid electrolytes, providing a basis for research and development and production.

[0007] To achieve the above object, the present invention provides a method for detecting the content of solid electrolyte in a battery pole piece, comprising:

[0008] Divide the battery pole piece to be tested into sampling areas, and prepare at least one pole piece cross-section test sample in each sampling area;

[0009] Obtain image data of each pole piece cross-section test sample, determine whether there are characteristic solid particles in each pole piece cross-section test sample based on the contrast parameters of the image data; determine characteristic solid particle distribution properties according to the proportion of pole piece cross-section test samples with characteristic solid particles in all pole piece cross-section test samples, and determine whether solid electrolyte is mixed in the battery pole piece to be tested according to the characteristic solid particle distribution properties; the characteristic solid particle distribution properties include: uniform distribution, non-uniform distribution and no distribution;

[0010] When it is determined that the battery pole piece to be tested is mixed with a solid electrolyte, an element type characterization test is performed on each pole piece cross-section test sample to obtain a characteristic element of the characteristic solid particle; wherein the characteristic element is one or more; and the characteristic element exists in the mixed solid electrolyte;

[0011] Separating the surface coating layer of one or more sampling areas of the battery pole piece to be tested to obtain a powder sample, characterizing the powder sample, determining the type of solid electrolyte mixed in the battery pole piece, and obtaining the molecular formula of the solid electrolyte;

[0012] The content of characteristic elements of the solid electrolyte mixed in the powder sample is determined, and when the characteristic solid particle distribution property is uniform distribution, the solid electrolyte mixing content in the battery electrode is determined based on the determined content combined with the molecular formula of the solid electrolyte.

[0013] Preferably, the sampling areas are distributed at different positions of the battery electrode to be tested;

[0014] The number of electrode cross-section test samples of a battery electrode to be tested shall be no less than 3;

[0015] The flatness of the pole piece cross section test sample is less than or equal to 3%.

[0016] Preferably, the acquiring of image data of each pole piece cross section test sample and determining whether characteristic solid particles exist in each pole piece cross section test sample based on contrast parameters of the image data specifically comprises:

[0017] For each pole piece cross section test sample, image data of the pole piece cross section test sample is obtained, and pixel area division processing is performed on the image data to obtain brightness parameters of each pixel area;

[0018] The maximum difference among the differences of the brightness parameters of adjacent pixel regions in the image data is used as the contrast parameter of the electrode cross section test sample;

[0019] When the contrast parameter is greater than or equal to a preset threshold, it is determined that the characteristic solid particles exist in the pole piece cross-section test sample; otherwise, the characteristic solid particles do not exist.

[0020] Further preferably, the brightness parameter of each pixel area is calibrated based on 11 levels in the Munsell color system;

[0021] The preset threshold value is 3 levels.

[0022] Preferably, determining the characteristic solid particle distribution attribute according to the proportion of the pole piece cross-section test samples having characteristic solid particles in all pole piece cross-section test samples, and determining whether the solid electrolyte is mixed in the battery pole piece to be tested according to the characteristic solid particle distribution attribute specifically includes:

[0023] When the characteristic solid particles are present in greater than or equal to 75% of the electrode cross-section test samples among all the electrode cross-section test samples, it is determined that the characteristic solid particles are uniformly distributed, and it is determined that the solid electrolyte is mixed in the battery electrode to be tested;

[0024] When the characteristic solid particles exist in more than 0 and less than 75% of the electrode cross-section test samples among all the electrode cross-section test samples, it is determined that the characteristic solid particle distribution attribute is non-uniform distribution, and it is determined that the solid electrolyte is mixed in the battery electrode to be tested;

[0025] When the characteristic solid particles do not exist in all the electrode cross-section test samples, it is determined that the characteristic solid particle distribution attribute is non-distributed, and it is determined that no solid electrolyte is mixed in the battery electrode to be tested.

[0026] Preferably, the particle size of the characteristic solid particles is 100 nanometers to 5 micrometers.

[0027] Preferably, the step of separating the surface coating layer of one or more sampling areas of the battery electrode to be tested to obtain a powder sample specifically includes:

[0028] The surface coating layer of each sampling area of ​​the battery electrode to be tested is scraped and separated from the current collector, and the powders obtained by scraping and separating the surface coating layers of each sampling area are mixed, and the powder sample is obtained after grinding, adding solvent to dissolve, centrifuging, settling, and drying.

[0029] Preferably, the method for determining the content of characteristic elements of the solid electrolyte mixed in the powder sample comprises: using one or more of an inductively coupled plasma emission spectrometer, an element analyzer, a chromatograph or a mass spectrometer to determine the content of characteristic elements of the solid electrolyte mixed in the powder sample;

[0030] The solid electrolyte includes: one or more of an oxide solid electrolyte, a sulfide electrolyte, a halide solid electrolyte, and a polymer electrolyte;

[0031] Among them, the characteristic elements of the oxide solid electrolyte include: one or more of phosphorus, aluminum, zirconium, lanthanum, and titanium; the characteristic elements of the sulfide solid electrolyte include: one or more of sulfur, germanium, and tin; the characteristic elements of the halide solid electrolyte include: one or more of fluorine, chlorine, bromine, iodine, indium, and strontium; the characteristic elements of the polymer electrolyte include: one or more of hydrogen, nitrogen, and carbon.

[0032] Preferably, the battery electrode to be tested is an original electrode for a secondary battery cell or an electrode obtained by disassembling a secondary battery cell;

[0033] The secondary battery includes: one or more of a lithium ion battery, a sodium ion battery, a potassium ion battery, and a zinc ion battery;

[0034] The secondary battery is a secondary battery in an original state or a secondary battery after cycle aging.

[0035] Further preferably, the secondary battery cell comprises: one or more of a hard shell cell, a soft pack cell, a cylindrical cell, or cells of other structures and shapes.

[0036] The method for detecting the content of solid electrolyte blending in a battery pole piece provided by the embodiment of the present invention combines multiple detection methods such as morphology, structure and composition characterization, and can effectively detect the distribution and content of solid electrolyte in the pole piece. First, by characterizing the morphology of the pole piece cross section, it is possible to quickly determine whether the pole piece is mixed with solid electrolyte, and by characterizing the elements, the characteristic elements of the solid electrolyte can be obtained; then, the powder sample coated on the surface of the pole piece is extracted, and the molecular formula of the solid electrolyte can be obtained by characterization, and the content of the characteristic elements of the solid electrolyte can be obtained by element content test analysis, and the content of the solid electrolyte in the battery pole piece is calculated in combination with the molecular formula of the solid electrolyte. The present invention can efficiently and accurately characterize the type and content of the solid electrolyte blending in the battery pole piece by combining the pole piece cross section detection and powder detection. The detection method of the present invention has good versatility, high detection accuracy, and is easy to promote. It can be applied to pole piece samples, as well as the original pole pieces and cycled pole pieces of various batteries such as soft-pack batteries, hard-shell batteries, and cylindrical batteries for detection, which is of great significance for the optimization analysis of the pole piece blending with solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A flow chart of a method for detecting the content of solid electrolyte blending in a battery pole piece provided by an embodiment of the present invention;

[0038] Figure 2 Scanning electron microscope (SEM) images of three cross-section test samples provided in Example 1 of the present invention;

[0039] Figure 3 The characteristic element distribution diagram obtained by characterizing the element types of characteristic solid particles using an energy dispersive X-ray spectrometer (EDS) for the three cross-section test samples provided in Example 1 of the present invention;

[0040] Figure 4 A structural diagram of the solid electrolyte mixed in the electrode provided in Example 1 of the present invention;

[0041] Figure 5 The cross-sectional morphology diagrams of the four pole piece cross-sectional test samples provided in Example 4 of the present invention;

[0042] Figure 6 These are cross-sectional morphology images of three pole piece cross-sectional test samples provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0044] The embodiment of the present invention provides a method for detecting the mixing content of solid electrolyte in a battery pole piece, which can be used to effectively detect the mixing content of solid electrolyte in various types of battery pole pieces.

[0045] Figure 1 The flow chart of the method for detecting the content of solid electrolyte in the battery pole piece provided by the embodiment of the present invention mainly includes the following steps. Figure 1 , the technical solution of the present invention is described.

[0046] Step 110, dividing the battery electrode to be tested into sampling areas, and preparing at least one electrode cross-section test sample in each sampling area.

[0047] The battery pole piece to be tested applicable to the present invention may be an original pole piece for a secondary battery cell or a pole piece obtained by disassembling a secondary battery cell; the secondary battery cell includes: one or more of a hard shell cell, a soft pack cell, a cylindrical cell or a cell of other structures and shapes. The secondary battery may be one or more of a lithium ion battery, a sodium ion battery, a potassium ion battery, and a zinc ion battery; its state may be an original state or a state after cycle aging.

[0048] The principle of dividing the sampling area for the battery pole piece to be tested is that the sampling covers all positions of the battery pole piece, that is, the sampling areas are distributed at different positions of the battery pole piece to be tested. For example, the battery pole piece is evenly divided into three areas of upper, middle and lower from top to bottom, and each area is used as a sampling area to select and prepare the pole piece cross-section test sample; or the battery pole piece is divided into four areas according to a cross, and each area is used as a sampling area to select and prepare the pole piece cross-section test sample. The purpose of this is to enable the pole piece cross-section test sample to truly and comprehensively characterize the overall situation of the battery pole piece to be tested. In the specific implementation of the present invention, the number of pole piece cross-section test samples of a battery pole piece to be tested is not less than 3.

[0049] When preparing the electrode section test sample, a thickness meter is used to measure the thickness of the battery electrode in each sampling area, and the thickness measurement error of multiple test points is controlled within 3%, and the position with good flatness in the area is cut to prepare the electrode section test sample. That is, the flatness of the electrode section test sample is less than or equal to 3%.

[0050] Step 120, obtaining image data of each pole piece cross-section test sample, determining whether there are characteristic solid particles in each pole piece cross-section test sample based on the contrast parameters of the image data; determining the characteristic solid particle distribution properties according to the proportion of pole piece cross-section test samples with characteristic solid particles in all pole piece cross-section test samples, and determining whether the battery pole piece to be tested is mixed with a solid electrolyte according to the characteristic solid particle distribution properties.

[0051] Specifically, for each pole piece cross-section test sample, image data of the pole piece cross-section test sample is obtained, and the image data is divided into pixel areas to obtain the brightness parameters of each pixel area; the maximum difference among the differences in the brightness parameters of each adjacent pixel area in the image data is used as the contrast parameter of the pole piece cross-section test sample; when the contrast parameter is greater than or equal to a preset threshold, it is determined that the characteristic solid particles exist in the pole piece cross-section test sample, otherwise the characteristic solid particles do not exist.

[0052] Among them, to obtain the image data of the pole piece cross-section test sample, the microscope imaging technology can be used to select the appropriate resolution and magnification, and the microscope field image can be captured as an image file through the imaging software. Furthermore, the existing image processing software can be used to remove noise, adjust contrast, etc. to optimize the image quality.

[0053] The pixel region division of image data can be realized by using the commonly used methods in image processing such as equally divided grid or dynamic region division (such as sliding window or adaptive threshold segmentation). A pixel region includes multiple pixels. For example, a pixel region is a 10×10 pixel block.

[0054] The brightness parameter represents the brightness intensity of an area in an image, and can be extracted and processed from image data using a variety of existing technical methods, such as grayscale conversion, HSV / HSL color space conversion, and Lab color space conversion. The following examples illustrate:

[0055] When using the grayscale conversion method, the image corresponding to each pixel area can be converted into a grayscale image (single channel), and the grayscale value can directly represent the brightness of each pixel.

[0056] When using HSV / HSL color space conversion, the image corresponding to each pixel area is converted from RGB space to HSV (Hue, Saturation, Value) or HSL (Hue, Saturation, Lightness) color space, and the "V" or "L" channel is directly used as the brightness parameter.

[0057] When using Lab color space conversion, the image is converted to the Lab color space, and the "L" channel is taken as the brightness parameter, and the L value range is 0 to 100.

[0058] In addition, methods such as convolution filtering to extract local brightness and deep learning model estimation can be used to obtain brightness parameters.

[0059] In a specific embodiment of the present invention, the brightness parameter of each pixel area is calibrated using 11 levels based on the Munsell color system. In the Munsell color system, brightness is a parameter that measures the brightness of a color, and the level range is 0 (completely black) to 10 (completely white).

[0060] The specific processing process can be: convert the image from RGB to grayscale or Lab or HSV, extract the corresponding parameters, and then normalize to the Munsell range of 0-10. That is, for each divided pixel area, calculate the average value of its parameters and use it as the average brightness of the area. Map the brightness value to the Munsell brightness range of 0 to 10.

[0061] For example, if the brightness range of the original image is 0 to 255, then the Munsell brightness of the pixel region = the average brightness of the pixel region × 10 / 255. This method is only an example and is not used to limit the calculation method of the Munsell brightness in the present invention.

[0062] Based on Munsell brightness, the preset threshold is specified as 3 levels in this embodiment. The present invention uses the maximum difference in the difference of brightness parameters of each adjacent pixel area in the image data as the contrast parameter of the pole piece cross section test sample. The purpose of selecting the maximum brightness difference as the contrast parameter is to capture the most significant brightness changes in the image. This change can often reflect the differences in key feature areas in the sample, such as the presence of significantly different particles, that is, the characteristic solid particles mentioned in the present invention. If there is a brightness difference of 3 levels or more in the image data of the pole piece cross section test sample, it can be identified that there is a mixed solid electrolyte in the pole piece cross section test sample.

[0063] Furthermore, when characteristic solid particles exist in greater than or equal to 75% of the pole piece cross-section test samples among all the pole piece cross-section test samples, the characteristic solid particle distribution property is determined to be uniform distribution, and it is determined that the solid electrolyte is mixed in the battery pole piece to be tested; when characteristic solid particles exist in greater than 0 and less than 75% of the pole piece cross-section test samples among all the pole piece cross-section test samples, the characteristic solid particle distribution property is determined to be non-uniform distribution, and it is determined that the solid electrolyte is mixed in the battery pole piece to be tested; when characteristic solid particles do not exist in all the pole piece cross-section test samples, the characteristic solid particle distribution property is determined to be non-distributed, and it is determined that the solid electrolyte is not mixed in the battery pole piece to be tested.

[0064] Step 130, when it is determined that the battery pole piece to be tested is mixed with a solid electrolyte, an element type characterization test is performed on each pole piece cross-section test sample to obtain characteristic elements of characteristic solid particles;

[0065] An energy dispersive X-ray spectrometer (EDS) is used to characterize the element types and distribution of the cross-sectional test sample to obtain the constituent element composition of the characteristic solid particles, especially the composition of the characteristic elements. Among them, the characteristic element can be one or more; the characteristic element exists in the blended solid electrolyte. The "existing" mentioned here can be understood as the characteristic element only gathering in the blended solid electrolyte, and the area where the non-characteristic solid particles are located does not contain or only contains a trace amount of negligible characteristic elements. In the present invention, the particle size of the characteristic solid particles is 100 nanometers to 5 microns.

[0066] In addition, when it is determined that the solid electrolyte is not mixed in the battery electrode to be tested, the subsequent detection method is no longer executed.

[0067] Step 140, separating the surface coating layer of one or more sampling areas of the battery electrode to be tested to obtain a powder sample, characterizing the powder sample, determining the type of solid electrolyte mixed in the battery electrode, and obtaining the molecular formula of the solid electrolyte.

[0068] In order to ensure that the test results can fully and accurately reflect the situation of the entire battery electrode, it is preferred that the surface coating layer of each sampling area of ​​the battery electrode to be tested is scraped and separated from the current collector, and the post-scraping treatment process also includes: mixing the powders obtained by scraping and separating the surface coating layers of each sampling area, grinding, adding solvent to dissolve, centrifuging, settling, and drying to obtain a powder sample. Use an X-ray diffractometer to perform structural characterization on the powder sample, determine the type of solid electrolyte mixed in the electrode, and obtain the molecular formula of the solid electrolyte, or use chromatography / mass spectrometry technology to characterize the composition of the soaking liquid for scraping the electrode to determine the molecular formula of the polymer solid electrolyte mixed in the electrode. Among them, the use of an X-ray diffractometer to perform structural characterization on the powder sample is applicable to oxide solid electrolytes, sulfide electrolytes, and halide solid electrolytes; the use of chromatography / mass spectrometry technology to perform component characterization on the soaking liquid for scraping the electrode is applicable to polymer electrolytes.

[0069] More preferably, the specific process of separating the surface coating layer to obtain a powder sample is as follows: after using a scraper to complete the powder scraping, for each sampling area, weigh the same mass of powder and put it into a mortar to grind the scraped powder, and then dissolve the ground powder in dichloromethane and / or acetonitrile solvent, the solid-liquid mass ratio can be 1:5-1:15, and most preferably 1:10. The powder is dissolved evenly by oscillation, and then placed in a centrifuge for centrifugation at a speed of 8000-15000 rpm. After the centrifugation, the upper clear liquid is poured out, and the precipitated powder is placed in an oven at 100-120°C for 6-12 hours for heating and drying to obtain a powder sample. The process of obtaining the soaking liquid for the electrode scraping powder is as follows: after the scraping powder is completed using a scraper, the scraping powder is soaked in dichloromethane and / or N,N-dimethylformamide solvent, and the mixed solution is stirred with a stirrer to make the scraping powder fully dissolved in the solvent, and then the upper clear liquid is taken, and the upper clear liquid is filtered with a 0.22um filter membrane to obtain the soaking liquid for the electrode scraping powder.

[0070] Step 150, determining the content of characteristic elements of the solid electrolyte mixed in the powder sample, and, when the characteristic solid particle distribution property is uniform distribution, determining the solid electrolyte mixing content in the battery electrode according to the determined content combined with the molecular formula of the solid electrolyte.

[0071] Specifically, the method for determining the content of characteristic elements of the solid electrolyte mixed in the powder sample includes: using one or more of an inductively coupled plasma emission spectrometer, an element analyzer, a chromatograph, or a mass spectrometer to determine the content of characteristic elements of the solid electrolyte mixed in the powder sample. Among them, the inductively coupled plasma emission spectrometer can be used to determine the characteristic elements of the inorganic component, and the element analyzer can be used to determine the characteristic elements of the organic component.

[0072] The percentage content of the solid electrolyte in the powder sample can be calculated based on the molecular formula of the solid electrolyte and the content of characteristic elements.

[0073] The solid electrolyte in the present invention includes: one or more of oxide solid electrolyte, sulfide electrolyte, halide solid electrolyte, polymer electrolyte. Among them, the characteristic elements of oxide solid electrolyte include: one or more of phosphorus, aluminum, zirconium, lanthanum, titanium; the characteristic elements of sulfide solid electrolyte include: one or more of sulfur, germanium, tin; the characteristic elements of halide solid electrolyte include: one or more of fluorine, chlorine, bromine, iodine, indium, strontium; the characteristic elements of polymer electrolyte include: one or more of hydrogen, nitrogen, carbon.

[0074] The method for detecting the content of solid electrolyte blending in a battery pole piece provided in an embodiment of the present invention combines a variety of detection methods such as morphology, structure and composition characterization, and can effectively detect the distribution and content of the solid electrolyte in the pole piece. First, by characterizing the morphology of the pole piece cross section, it is possible to quickly determine whether a solid electrolyte is mixed in the pole piece, and by element characterization, the characteristic elements of the solid electrolyte can be obtained; then, a powder sample coated on the surface of the pole piece is extracted, and the molecular formula of the solid electrolyte can be obtained by characterization, and the content of the characteristic elements of the solid electrolyte can be obtained by element content test analysis, and the content of the solid electrolyte in the battery pole piece is calculated in combination with the molecular formula of the solid electrolyte. The present invention can efficiently and accurately characterize the type and content of the blending of the solid electrolyte in the battery pole piece by combining pole piece cross section detection with powder detection.

[0075] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] The batteries, materials and reagents used in the embodiments of the present invention can be obtained from the market or homemade.

[0077] Example 1

[0078] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of a homemade liquid soft-pack lithium-ion battery negative electrode plate.

[0079] The positive electrode in the battery system uses LiNi 0.6 Co 0.2 Mn 0.2 O2 material, the negative electrode uses graphite negative electrode material, the electrolyte uses 1 mol / L LiPF6, and the solvent is ethylene carbonate (EC): dimethyl carbonate (DEC): ethyl methyl carbonate (EMC) (vol:vol:vol=1:1:1). The blending content in the negative electrode sheet is known to be 4.3wt%, and the blended solid electrolyte is Li 1.3 Al 0.3 T i 1.7 (PO4) 3. The battery cycle is 3 weeks, the charge and discharge voltage is 3.0-4.6V, and the rate is 0.5C.

[0080] The detection process is as follows:

[0081] (1) Pole piece sample pretreatment: The soft-pack battery cell is non-destructively disassembled to obtain the negative electrode piece, and the upper, middle and lower parts are selected as three sampling areas, and a flat area with a flatness of less than or equal to 3% is selected from each of them. Three pole piece cross-section test samples are prepared using an ion cutting instrument.

[0082] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscopy and energy dispersive X-ray spectrometer were used to characterize the types and distribution of elements in three electrode cross-section test samples. It was found that characteristic solid particles with different contrasts existed in the electrode cross-section test samples. The scanning electron microscopy images of the three electrode cross-section test samples were as follows: Figure 2 a-2c. According to the 11 levels in the Munsell color system, there are obvious characteristic solid particles in the three electrode cross-section test samples. Because the brightness difference between the characteristic solid particles and the surrounding test area is 3 levels, that is, the contrast parameter is equal to the preset threshold, it is determined that the sample is mixed with solid electrolyte. The measured particle size is 100 nanometers to 500 nanometers. The element type of the characteristic solid particles is characterized using an energy dispersive X-ray spectrometer (EDS), as shown in FIG. Figure 3 As shown in a-3c, the equipment identified the characteristic element of the characteristic solid particle as aluminum, and the results of the energy dispersive X-ray spectrometer showed that the aluminum element was relatively dense at the characteristic solid particle compared with other surrounding environments.

[0083] (3) Characterize the structure of the solid electrolyte in the battery electrode: Use a scraper to scrape the surface coating layer of each sampling area of ​​the negative electrode, mix the scraped powder of the same mass in each sampling area, and take the same mass of scraped powder from each sampling area from the remaining scraped powder of each sampling area for use in step (4). Grind the mixed scraped powder with a mortar, and then dissolve the ground solid powder in acetonitrile solvent, wherein the mass ratio of acetonitrile solvent to solid powder is 10:1. The powder is evenly dissolved by oscillation, and then placed in a centrifuge for centrifugation at a speed of 10,000 rpm. After the centrifugation, the upper clear liquid is poured out, and the precipitated powder is placed in an oven for heating and drying at 100°C for 6 hours. After drying, the precipitated powder is characterized by structure using an X-ray diffraction (XRD) instrument. The results are as follows: Figure 4 As shown, the solid electrolyte mixed in the sample is determined by XRD test to be Li 1.3 A l 0.3 T i 1.7 (PO4)3.

[0084] (4) Detection of the solid electrolyte content in the battery pole piece: The aluminum content in the negative electrode piece was characterized using an inductively coupled plasma emission spectrometer. The scraping powder left in each sampling area in the previous step was tested separately. The aluminum contents of the three sampling areas were 0.786ug / mg, 0.926ug / mg, and 0.889ug / mg, respectively. The final calculated average aluminum content was 0.867ug / mg.

[0085] (5) Molecular formula Li combined with solid electrolyte 1.3 A l 0.3 T i 1.7 (PO4)3 (molecular weight is 383.37) to determine the mixing content of the solid electrolyte: in the molecular formula, the mass proportion of aluminum element is 0.021. According to the average content of aluminum element of 0.867ug / mg, it is calculated that the content of solid electrolyte mixed in the negative electrode material is about 41.285ug / mg, that is, the mixing content is 4.129wt%, which is only 4% error compared with the known mixing amount.

[0086] Example 2

[0087] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of a homemade hybrid solid-liquid hard-shell lithium-ion battery positive electrode plate.

[0088] The positive electrode in the battery system uses LiNi 0.8 Co 0.1 Mn 0.1 O2 material, the negative electrode uses silicon negative electrode material, the liquid electrolyte uses 1 mol / L LiPF6, the solvent is ethylene carbonate (EC): dimethyl carbonate (DMC) (vol:vol=1:1), the additive is 1% FEC, and the solid electrolyte uses Li7La3Zr2O 12 The content of the positive electrode is known to be 3wt%, and the solid electrolyte is Li 0.33 La 0.557 TiO3. The battery cycle number is 0.

[0089] The detection process is as follows:

[0090] (1) Pole piece sample pretreatment: The hard shell battery cell is non-destructively disassembled to obtain the positive electrode piece, which is divided into 5 sampling areas from top to bottom. A flat area with a flatness of less than or equal to 3% is selected from each area, and 5 pole piece cross-section test samples are prepared using an ion cutting instrument.

[0091] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscope and energy dispersive X-ray spectrometer were used to characterize the element types and distribution in the five electrode section test samples. It was found that there were characteristic solid particles with different contrasts in the electrode section test samples. According to the 11 levels in the Munsell color system, there were obvious characteristic solid particles in the five electrode section test samples. Because the brightness difference between the characteristic solid particles and the surrounding test area was 4 levels, that is, the contrast parameter was greater than the preset threshold, it was determined that the sample was mixed with solid electrolytes. The measured particle size was 1 micron-5 microns. The element type of the characteristic solid particles was characterized by an energy dispersive X-ray spectrometer (EDS). The equipment identified the characteristic element of the characteristic solid particles as lanthanum. The results of the energy dispersive X-ray spectrometer showed that compared with other surrounding environments, lanthanum was relatively dense at the characteristic solid particles.

[0092] (3) Characterizing the structure of the solid electrolyte in the battery electrode: Use a scraper to scrape the surface coating layer of each sampling area of ​​the positive electrode, mix the scraped powder of the same mass in each sampling area, and take the scraped powder of the same mass from each sampling area from the remaining scraped powder of each sampling area for use in step (4). Grind the mixed scraped powder with a mortar, and then dissolve the ground solid powder in a dichloromethane solvent, wherein the mass ratio of dichloromethane solvent to solid powder is 10:1. The powder is evenly dissolved by oscillation, and then placed in a centrifuge for centrifugation at a speed of 8000 rpm. After the centrifugation is completed, the upper clear liquid is poured out, and the precipitated powder is placed in an oven at 120°C for 10 hours for heating and drying. After drying, the precipitated powder is characterized by an X-ray diffractometer. The solid electrolyte mixed in the sample is determined to be Li by XRD test. 0.33 La 0.557 TiO3.

[0093] (4) Detection of the solid electrolyte content in the battery electrode: The lanthanum content in the positive electrode was characterized by using an inductively coupled plasma emission spectrometer. The scraping powder left in each sampling area in the previous step was tested separately. The lanthanum contents at the five locations were 11.756ug / mg, 13.254ug / mg, 12.966ug / mg, 12.134ug / mg and 12.640ug / mg, respectively. The average lanthanum content at the five locations was 12.550ug / mg.

[0094] (5) Molecular formula Li combined with solid electrolyte 0.33 La 0.557TiO3 (molecular weight 175.54) determines the blending content of the solid electrolyte: in the molecular formula, the mass proportion of the lanthanum element is 0.44. Based on the lanthanum content of 12.550ug / mg, it is calculated that the content of the solid electrolyte mixed in the positive electrode material is approximately 28.523ug / mg, that is, the blending content is 2.852wt%, which is only 4.93% error compared with the known blending amount.

[0095] Example 3

[0096] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of a homemade solid-state soft-pack lithium-ion battery positive electrode plate.

[0097] The positive electrode in the battery system uses Li CoO2 material, the negative electrode uses metallic lithium, and the solid electrolyte uses Li3YC l6. The content of the mixed content in the positive electrode plate is known to be 1wt%, and the mixed solid electrolyte is Li3YC l6. The battery cycle is 10 weeks, the charge and discharge voltage is 3.0-4.6V, and the rate is 0.1C.

[0098] The detection process is as follows:

[0099] (1) Pole piece sample pretreatment: The soft-pack battery cell is non-destructively disassembled to obtain the positive electrode piece, which is divided into four sampling areas from top to bottom. A flat area with a flatness of less than or equal to 3% is selected from each area, and four pole piece cross-section test samples are prepared using an ion cutting instrument.

[0100] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscope and energy dispersive X-ray spectrometer were used to characterize the element types and distribution in the four electrode cross-section test samples. It was found that there were characteristic solid particles with different contrasts in the electrode cross-section test samples. According to the 11 levels in the Munsell color system, there were obvious characteristic solid particles in the four electrode cross-section test samples. Because the brightness difference between the characteristic solid particles and the surrounding test area was 3 levels, that is, the contrast parameter was equal to the preset threshold, it was determined that the sample was mixed with solid electrolytes. The measured particle size was 500 nanometers-2 microns. The element type of the characteristic solid particles was characterized by an energy dispersive X-ray spectrometer (EDS). The equipment identified the characteristic element of the characteristic solid particles as chlorine. The results of the energy dispersive X-ray spectrometer showed that the chlorine element was relatively dense at the characteristic solid particles compared with other surrounding environments.

[0101] (3) Characterizing the structure of the solid electrolyte in the battery pole piece: Use a scraper to scrape the surface coating layer of each sampling area of ​​the positive electrode pole piece, mix the scraped powder of the same mass in each sampling area, and take the scraped powder of the same mass from each sampling area in the remaining scraped powder of each sampling area for use in step (4). Grind the mixed scraped powder with a mortar, and then dissolve the ground solid powder in acetonitrile solvent, wherein the mass ratio of acetonitrile solvent to solid powder is 10:1, and the powder is evenly dissolved by oscillation, and then placed in a centrifuge for centrifugation at a speed of 15,000 rpm. After the centrifugation, pour out the upper clear liquid, put the precipitated powder in an oven at 100°C for 10 hours for heating and drying, and after drying, use an X-ray diffractometer to characterize the structure of the precipitated powder, and determine that the solid electrolyte mixed in the sample is Li3YCl6 through XRD testing.

[0102] (4) Detection of the solid electrolyte content in the battery electrode: The chlorine content in the positive electrode was characterized by using an inductively coupled plasma emission spectrometer. The scraping powder left in each sampling area in the previous step was tested separately. The chlorine contents at the four locations were 5.639ug / mg, 5.990ug / mg, 5.993ug / mg and 6.158ug / mg, respectively. The average chlorine content at the four locations was 5.945ug / mg.

[0103] (5) The mixing content of the solid electrolyte is determined based on the molecular formula of the solid electrolyte Li3YCl6 (molecular weight 322.60): In the molecular formula, the mass proportion of the chlorine element is 0.659. Based on the chlorine content of 5.945ug / mg, the content of the solid electrolyte mixed in the positive electrode material is calculated to be approximately 9.021ug / mg, that is, the mixing content is 0.902wt%, which is only 9.80% error compared with the known mixing amount.

[0104] Example 4

[0105] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of a homemade solid-state soft-pack lithium-ion battery negative electrode plate.

[0106] The positive electrode in the battery system uses LiNi 0.6 Co 0.2 Mn 0.2 O2 material, the negative electrode uses graphite material, and the solid electrolyte uses Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The content of the mixed negative electrode is known to be 2.5wt%, and the mixed solid electrolyte is known to be Li 1.3 Al 0.3 Ti1.7 (PO4) 3. The battery cycle is 10 weeks, the charge and discharge voltage is 3-4.6V, and the rate is 0.1C.

[0107] The detection process is as follows:

[0108] (1) Electrode sample pretreatment: The soft-pack battery cell is non-destructively disassembled to obtain the negative electrode, which is divided into four sampling areas from top to bottom. A flat area with a flatness of less than or equal to 3% is selected from each area, and four electrode cross-section test samples are prepared using an ion cutting instrument.

[0109] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscopy and energy dispersive X-ray spectrometer were used to characterize the element types and distribution in four electrode cross-section test samples. It was found that there were no characteristic solid particles with different contrast in two of the electrode cross-section test samples, such as Figure 5 As shown in a-5b, the other two pole piece cross-section test samples have characteristic solid particles with different contrasts, such as Figure 5 As shown in c-5d; according to the 11 levels in the Munsell color system, in the sample with characteristic solid particles of different contrast, the brightness difference between the characteristic solid particles and the surrounding test area is 3 levels, that is, the contrast parameter is equal to the preset threshold value, which determines that the sample is mixed with solid electrolyte, but the uniformity is not very good. The measured particle size is 1 micron-2 microns. The element type of the characteristic solid particles was characterized using an energy dispersive X-ray spectrometer (EDS). The equipment identified the characteristic element of the characteristic solid particles as aluminum. The results of the energy dispersive X-ray spectrometer showed that the aluminum element was relatively dense at the characteristic solid particles compared with other surrounding environments.

[0110] (3) Characterize the structure of the solid electrolyte in the battery pole piece: Use a scraper to scrape the surface coating layer of the sampling area of ​​the two initial characteristic solid particles of the negative pole piece, mix the scraped powder of the same mass in the two sampling areas, and take the same mass of scraped powder from the remaining scraped powder for use in step (4). Grind the mixed scraped powder with a mortar, and then dissolve the ground solid powder in acetonitrile solvent, wherein the mass ratio of acetonitrile solvent to solid powder is 10:1. The powder is evenly dissolved by oscillation, and then placed in a centrifuge for centrifugation at a speed of 11,000 rpm. After the centrifugation, the upper clear liquid is poured out, and the precipitated powder is placed in an oven at 120°C for 6 hours for heating and drying. After drying, the precipitated powder is characterized by an X-ray diffractometer. The solid electrolyte mixed in the sample is determined to be Li by XRD test. 1.3 A l 0.3 Ti 1.7 (PO4)3.

[0111] (4) Detection of the solid electrolyte content in the battery pole piece: Use an inductively coupled plasma emission spectrometer to characterize the aluminum content in the negative electrode plate, and test the scraping powder left in the two sampling areas in the previous step separately. The aluminum content at the two locations was 0.483ug / mg and 0.465ug / mg respectively. Finally, the average aluminum content at the two locations was 0.474ug / mg.

[0112] (5) Molecular formula Li combined with solid electrolyte 1.3 A l 0.3 T i 1.7 (PO4)3 (molecular weight is 383.37) to determine the solid electrolyte mixing content in the battery pole piece: in the molecular formula, the mass proportion of aluminum element is 0.021. According to the aluminum content of 0.474ug / mg, it is calculated that the content of the mixed solid electrolyte in the above two sampling areas is about 22.571ug / mg, that is, the mixing content is 2.257wt%. However, since the pole piece is non-uniformly doped, the solid electrolyte mixing content in the above two sampling areas cannot reflect the mixing content in the entire battery pole piece. Therefore, for the non-uniformly doped pole piece, only the mixing content of the sampling area can be obtained, but the mixing content of the entire pole piece cannot be obtained.

[0113] Example 5

[0114] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of a homemade liquid soft-pack lithium-ion battery negative electrode plate.

[0115] The positive electrode in the battery system uses LiNi 0.6 Co 0.2 Mn 0.2 O2 material, graphite material for the negative electrode, 1 mol / L Li PF6 electrolyte, ethylene carbonate (EC): dimethyl carbonate (DEC): ethyl methyl carbonate (EMC) (vol:vol:vol=1:1:1) solvent. No solid electrolyte was mixed in the negative electrode. The battery cycle was 5 weeks, the charge and discharge voltage was 3.0-4.6V, and the rate was 1C.

[0116] The detection process is as follows:

[0117] (1) Electrode sample pretreatment: The soft-pack battery cell is non-destructively disassembled to obtain the negative electrode, which is divided into three sampling areas from top to bottom. A flat area with a flatness of less than or equal to 3% is selected from each area, and three electrode cross-section test samples are prepared using an ion cutting instrument.

[0118] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscopy and energy dispersive X-ray spectrometer were used to characterize the types and distribution of elements in the three electrode section test samples. It was found that there were no characteristic solid particles with different contrasts in the electrode section. According to the 11 levels in the Munsell color system, the overall brightness difference of the test area of ​​the current electrode section test sample was 2 levels, that is, the contrast parameter was lower than the preset threshold, such as Figure 6 As shown in a-6c, it is confirmed that no solid electrolyte is mixed in the sample.

[0119] Example 6

[0120] This embodiment uses a solid electrolyte blending content detection method to detect the solid electrolyte blending content of purchased solid-state soft-pack lithium-ion battery positive electrode plates.

[0121] The positive electrode in the battery system uses LiNi 0.6 Co 0.2 Mn 0.2 O2 material, the negative electrode uses C@SiO material, and the solid electrolyte uses Li 1.3 Al 0.3 T i 1.7 (PO4)3. The content of the positive electrode and the type of solid electrolyte are unknown. The battery cycle is 1 week, 2.5-4.8V, and the rate is 0.2C.

[0122] The detection process is as follows:

[0123] (1) Pole piece sample pretreatment: The soft-pack battery cell is non-destructively disassembled to obtain the positive electrode piece, and the upper, middle and lower parts are selected as three sampling areas, and a flat area with a flatness of less than or equal to 3% is selected from each of them. Three pole piece cross-section test samples are prepared using an ion cutting instrument.

[0124] (2) Characterization of the distribution of solid electrolytes in battery electrodes: Scanning electron microscope and energy dispersive X-ray spectrometer were used to characterize the element types and distribution in the three electrode cross-section test samples, and it was found that characteristic solid particles with different contrasts existed in the electrode cross-section test samples. According to the 11 levels in the Munsell color system, there were obvious characteristic solid particles in the three electrode cross-section test samples, because the brightness difference between the characteristic solid particles and the surrounding test area was 4 levels, that is, the contrast parameter was greater than the preset threshold, which determined that the solid electrolyte was mixed in the sample. The measured particle size was 1 micron-3 microns. The element type of the characteristic solid particles was characterized using an energy dispersive X-ray spectrometer (EDS). The equipment identified the characteristic element of the characteristic solid particles as aluminum. The results of the energy dispersive X-ray spectrometer showed that the aluminum element was relatively dense at the characteristic solid particles compared with other surrounding environments.

[0125] (3) Characterizing the structure of the solid electrolyte in the battery pole piece: Use a scraper to scrape the surface coating layer of each sampling area of ​​the positive electrode pole piece, mix the scraped powder of the same mass in each sampling area, and take the scraped powder of the same mass from each sampling area in the remaining scraped powder of each sampling area for use in step (4). Grind the mixed scraped powder with a mortar, and then dissolve the ground solid powder in acetonitrile solvent, wherein the mass ratio of acetonitrile solvent to solid powder is 10:1, and the powder is evenly dissolved by oscillation, and then placed in a centrifuge for centrifugation at a speed of 13,000 rpm. After the centrifugation is completed, the upper clear liquid is poured out, and the precipitated powder is placed in an oven at 110°C for 8 hours for heating and drying. After drying, an X-ray diffraction (XRD) instrument is used to characterize the structure of the precipitated powder. The XRD test determines that the solid electrolyte mixed in the sample is Li 1.3 A l 0.3 T i 1.7 (PO4)3.

[0126] (4) Detection of the solid electrolyte content in the battery electrode: The aluminum content in the positive electrode was characterized using an inductively coupled plasma emission spectrometer. The scraping powder left in each sampling area in the previous step was tested separately. The aluminum contents of the three sampling areas were 0.405 ug / mg, 0.378 ug / mg, and 0.516 ug / mg, respectively. The final calculated average aluminum content was 0.433 ug / mg.

[0127] (5) Molecular formula Li combined with solid electrolyte 1.3 A l 0.3 T i 1.7 (PO4)3 (molecular weight is 383.37) to determine the blending content of the solid electrolyte: In the molecular formula, the mass proportion of the aluminum element is 0.021. Based on the average content of the aluminum element of 0.433ug / mg, it is calculated that the content of the solid electrolyte mixed in the positive electrode material is approximately 20.619ug / mg, that is, the blending content is 2.061wt%.

[0128] It can be seen from the above embodiments that the detection means of the present invention has good versatility, high detection accuracy, and is easy to promote. It can be applied to the detection of electrode samples, as well as original electrode pieces and cycled electrode pieces of various battery cells such as soft-pack battery cells, hard-shell battery cells, and cylindrical battery cells, and is of great significance for the optimization analysis of electrode-blended solid electrolytes.

[0129] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for detecting the content of solid electrolyte in a battery pole piece, characterized in that: The test method includes: Divide the battery pole piece to be tested into sampling areas, and prepare at least one pole piece cross-section test sample in each sampling area; Obtain image data of each pole piece cross-section test sample, determine whether there are characteristic solid particles in each pole piece cross-section test sample based on the contrast parameters of the image data; determine characteristic solid particle distribution properties according to the proportion of pole piece cross-section test samples with characteristic solid particles in all pole piece cross-section test samples, and determine whether solid electrolyte is mixed in the battery pole piece to be tested according to the characteristic solid particle distribution properties; the characteristic solid particle distribution properties include: uniform distribution, non-uniform distribution and no distribution; When it is determined that the battery pole piece to be tested is mixed with a solid electrolyte, an element type characterization test is performed on each pole piece cross-section test sample to obtain a characteristic element of the characteristic solid particle; wherein the characteristic element is one or more; and the characteristic element exists in the mixed solid electrolyte; Separating the surface coating layer of one or more sampling areas of the battery pole piece to be tested to obtain a powder sample, characterizing the powder sample, determining the type of solid electrolyte mixed in the battery pole piece, and obtaining the molecular formula of the solid electrolyte; The content of characteristic elements of the solid electrolyte mixed in the powder sample is determined, and when the characteristic solid particle distribution property is uniform distribution, the solid electrolyte mixing content in the battery electrode is determined based on the determined content combined with the molecular formula of the solid electrolyte.

2. The testing method according to claim 1, characterized in that: The sampling areas are distributed at different positions of the battery electrode to be tested; The number of electrode cross-section test samples of a battery electrode to be tested shall be no less than 3; The flatness of the pole piece cross section test sample is less than or equal to 3%.

3. The testing method according to claim 1, characterized in that: The step of acquiring image data of each pole piece cross section test sample and determining whether there are characteristic solid particles in each pole piece cross section test sample based on the contrast parameters of the image data specifically includes: For each pole piece cross section test sample, image data of the pole piece cross section test sample is obtained, and pixel area division processing is performed on the image data to obtain brightness parameters of each pixel area; The maximum difference among the differences of the brightness parameters of adjacent pixel regions in the image data is used as the contrast parameter of the electrode cross section test sample; When the contrast parameter is greater than or equal to a preset threshold, it is determined that the characteristic solid particles exist in the pole piece cross-section test sample; otherwise, the characteristic solid particles do not exist.

4. The testing method according to claim 3, characterized in that: The brightness parameter of each pixel area is calibrated based on 11 levels in the Munsell color system; The preset threshold value is 3 levels.

5. The testing method according to claim 1, characterized in that: The method of determining the characteristic solid particle distribution attribute according to the proportion of the pole piece cross-section test samples having characteristic solid particles in all pole piece cross-section test samples, and determining whether the solid electrolyte is mixed in the battery pole piece to be tested according to the characteristic solid particle distribution attribute specifically includes: When the characteristic solid particles are present in greater than or equal to 75% of the electrode cross-section test samples among all the electrode cross-section test samples, it is determined that the characteristic solid particles are uniformly distributed, and it is determined that the solid electrolyte is mixed in the battery electrode to be tested; When the characteristic solid particles exist in more than 0 and less than 75% of the electrode cross-section test samples among all the electrode cross-section test samples, it is determined that the characteristic solid particle distribution attribute is non-uniform distribution, and it is determined that the solid electrolyte is mixed in the battery electrode to be tested; When the characteristic solid particles do not exist in all the electrode cross-section test samples, it is determined that the characteristic solid particle distribution attribute is non-distributed, and it is determined that no solid electrolyte is mixed in the battery electrode to be tested.

6. The testing method according to claim 1, characterized in that: The particle size of the characteristic solid particles is 100 nanometers to 5 micrometers.

7. The testing method according to claim 1, characterized in that: The step of separating the surface coating layer of one or more sampling areas of the battery electrode to be tested to obtain a powder sample specifically includes: The surface coating layer of each sampling area of ​​the battery electrode to be tested is scraped and separated from the current collector, and the powders obtained by scraping and separating the surface coating layers of each sampling area are mixed, and the powder sample is obtained after grinding, adding solvent to dissolve, centrifuging, settling, and drying.

8. The testing method according to claim 1, characterized in that: The method for determining the content of characteristic elements of the solid electrolyte mixed in the powder sample comprises: using one or more of an inductively coupled plasma emission spectrometer, an element analyzer, a chromatograph or a mass spectrometer to determine the content of characteristic elements of the solid electrolyte mixed in the powder sample; The solid electrolyte includes: one or more of an oxide solid electrolyte, a sulfide electrolyte, a halide solid electrolyte, and a polymer electrolyte; Among them, the characteristic elements of the oxide solid electrolyte include: one or more of phosphorus, aluminum, zirconium, lanthanum, and titanium; the characteristic elements of the sulfide solid electrolyte include: one or more of sulfur, germanium, and tin; the characteristic elements of the halide solid electrolyte include: one or more of fluorine, chlorine, bromine, iodine, indium, and strontium; the characteristic elements of the polymer electrolyte include: one or more of hydrogen, nitrogen, and carbon.

9. The testing method according to claim 1, characterized in that: The battery electrode to be tested is an original electrode for a secondary battery cell or an electrode obtained by disassembling a secondary battery cell; The secondary battery includes: one or more of a lithium ion battery, a sodium ion battery, a potassium ion battery, and a zinc ion battery; The secondary battery is a secondary battery in an original state or a secondary battery after cycle aging.

10. The testing method according to claim 9, characterized in that: The secondary battery cell includes: one or more of a hard shell cell, a soft pack cell, a cylindrical cell or cells of other structures and shapes.

Citation Information

Patent Citations

  • Method for detecting content of non-metallic inclusions in metal powder for additive manufacturing

    CN115144323A

  • Method for identifying distribution state of added elements in positive electrode or precursor material

    CN117420166A

  • Impurity measuring method and device

    CN1806167A

  • Alkaline Battery Electrolyte Useful for a Rechargeable Alkaline Electrochemical Cell

    US20180083320A1

Cited By

  • Method and device for detecting uniformity of lithium ion battery negative electrode SEI membrane

    CN121678553A